Revitalizing Marxist theory for today's capitalism - Zarembka, Paul; Desai, Radhika, 1963- (Emerald, 2011)
Amidst a capitalist crisis that has upturned mainstream orthodoxies, this volume underscores the importance of historical and materialist understandings of capitalist economies. Thus, fundamentally, it exposes the limitations of neoclassical economics' endogenous growth theory and how it, in fact, gropes for understandings well established within Marxism. It goes on to examine the relationship between the 'real' economy and 'finance', and also examines how mainstream accounts of stagnation and financialization suffer from an inability to distinguish between productive and unproductive labour. A related study of the financialization of the Turkish economy dovetails this analysis. The volume also questions the current understanding of the information economy and the value of knowledge on a Marxist basis. Finally, an historical re-examination of the Great Depression in light of the current Great Recession, throws new light on modern capitalisms crisis tendencies. The volume concludes with a critique of Lenin's economics, serving also to remind the reader that he is the only world leader who had deeply studied his own country's economy before eventually becoming its leader.
Keywords: Marxian economics.; Capitalism.; Dialectical materialism.; Economic history.; elektronické knihy; electronic books